Progress in Microbial Degradation of Feather Waste - Li, Qingxin (Frontiers in Microbiology, 2019)
Feathers are a major by-product from poultry industry. They are mainly composed of keratins which have wide applications in different fields. Due to the increasing production of feathers from poultry industries, the untreated feathers could become pollutants because of their resistance to protease degradation. Feathers are rich in amino acids, which makes them a valuable resource for being converted into fertilizer and animal feeds. Numerous bacteria and fungi exhibited capabilities to degrade chicken feathers by secreting enzymes such as keratinases, providing an economic and efficient way to convert feather-containing wastes into value-added products. This review summarizes recent progress in microbial degradation of feathers. The strains that are able to secrete keratinase are summarized. In addition, the enzymes critical for keratin degradation and their mechanism of action are discussed. Based on the accumulated studies, microbial degradation of feathers has a great potential to convert them into various products such as biofertilizer and animal feeds.